Hambatan dan Tantangan Pelaksanaan Pendidikan Kewarganegaraan di Perguruan Tinggi - Rosmadi, Maskarto Lucky Nara (Penerbit STKIP PGRI Bangkalan, 2018)
Citizenship education is a compulsory subject in all universities based on the Law on National Education System. Therefore, national education should be implemented in order to form an Indonesian human who has integrity to the nation and country. The purpose of this research is to know the implementation of civic education in universities as well as obstacles and challenges in the implementation. The research method used is descriptive analytical with qualitative approach. Data collection techniques consist of primary data obtained from respondents and secondary data in the form of literature, scientific journals both nationally and internationally. From the result of research, it is found that giving the course of civic education by lecturer is only theoretical only without accompanied by the implementation of student activities. In addition, the lecturers who hold the subjects of civic education have no competence in the field of state defense and do not get special training as lecturer of civic education from any institution. This requires support from the central government through the National Resilience Institute by providing training in the form of lecturer candidates courses for Pancasila Education and Citizenship Education courses.